Chitosan Nanoparticles: Shedding Light on Immunotoxicity and Hemocompatibility - Jesus, Sandra; Marques, Ana Patrícia; Duarte, Alana; Soares, Edna; Costa, João Panão; Colaço, Mariana; Schmutz, Mélanie; Som, Claudia; Borchard, Gerrit; Wick, Peter; Borges, Olga (Frontiers in Bioengineering and Biotechnology, 2020)
Nanoparticles (NPs) assumed an important role in the area of drug delivery. Although number of studies including NPs are growing over the last years, their side effects on the immune system are often ignored or omitted. One of the most studied polymers in the nano based drug delivery system field is chitosan (Chit). In the scientific literature, the physicochemical properties (molecular weight or deacetylation degree) of the chitosan, endotoxin contamination, and appropriate testing controls are rarely reported, they can strongly influence immunotoxicity results. The present work aimed to study the immunotoxicity of NPs produced with different DDA and MW Chit polymers and are benchmarked to the polymer itself. Chit NPs were prepared based on the ionic gelation of Chit with sodium tripolyphosphate (TPP). This method allowed the production of two different NPs: Chit 80 % NPs (80 % DDA) and Chit 93 % NPs (93 % DDA). In general, we found greater reduction in cell viability induced by Chit NPs than the respective Chit polymers when tested in vitro using human peripheral blood monocytes (PBMCs) or RAW 264.7 cell line. In addition, Chit 80 % NPs were more cytotoxic for PBMCs, increased reactive oxygen species (ROS) production (above 156 µg/mL) in the RAW 264.7 cell line and interfered with the intrinsic pathway of coagulation (at 1 mg/mL) when compared to Chit 93 % NPs. On the other hand, only Chit 93 % NPs induced platelet aggregation (at 2 mg/mL). Although Chit NPs and Chit polymers did not stimulate the nitric oxide (NO) production in RAW 264.7 cells, they induced a decrease in lipopolysaccharide (LPS)-induced NO production at all tested concentrations. None of Chit NPs and polymers caused hemolysis, nor induced PBMCs to secrete TNF-  and IL-6 cytokines. From the obtained results we concluded that the DDA of the Chit polymer and the size of Chit NPs influence the in vitro immunotoxicity results. As the NPs are more cytotoxic than the corresponding polymers, one should be careful in the extrapolation of trends from the polymer to the NPs, and in the comparisons among delivery systems prepared with different DDA chitosans.